Prevention of human milk-acquired cytomegalovirus infection in very-low-birth-weight infants - Mi Lim Chung; Heungsup Sung; Euiseok Jung; Byong Sop Lee; Ki Soo Kim; Ellen Ai-Rhan Kim (BMC, 2023)
Abstract Background The aim of the study was to determine the rate of cytomegalovirus virolactia in the human milk (HM) of mothers of VLBW infants, compare the CMV infection rates and the changes in CMV DNA viral load and nutrient profile among different HM preparation methods. Methods A prospective randomized controlled study was performed in infants with gestational age < 32 weeks or birth-weight < 1500 g admitted to neonatal intensive care unit of Asan Medical Center and Haeundae Paik Hospital who were given mother's own milk. Enrolled infants were randomized into three groups according to the HM preparation methods: freezing-thawing (FT), FT + low-temperature Holder pasteurization (FT + LP), and FT + high-temperature short-term pasteurization (FT + HP). Urine CMV culture and PCR were obtained at birth and at 4, 8, and 12 weeks. HM CMV culture and PCR were obtained at birth and at 3, 6, 9, and 12 weeks. Changes in macronutrients in HM was obtained at 4 ~ 6 weeks. Results Of 564 infants, 217 mothers (38.5%) produced CMV PCR positive milk. After exclusion, a total of 125 infants were randomized into the FT (n = 41), FT + LP (n = 42), and FT + HP (n = 42) groups, whose rate of HM-acquired CMV infection was 4.9% (n = 2), 9.5% (n = 4), and 2.4% (n = 1), respectively. Out of seven CMV infected infants, two infants fed with FT + LP HM developed CMV infection- associated symptoms. Ages at diagnoses were earlier (28.5 days after birth) and at younger post conceptional age (< 32 weeks) in comparison to infants with asymptomatic CMV infection. CMV DNA viral load significantly decreased after pasturizations, especially in FT + HP group. Conclusions HM-acquired symptomatic CMV infection rate is low and its impact on clinical course was not serious in our VLBW infants. However, evidences showing poor neurodevelopmental outcome in later life, we need to generate a guideline to protect VLBW infant form HM transmitted CMV infection. Based on our small sized study, we did not find any superiority in pasteurizing HM with frequently used LP in comparison to frozen or HP HM. More research is needed to determine the method and duration of pasteurization to reduce the HM-acquired CMV infection.